Perspective: Growth monitoring and promotion as an opportunity to improve early childhood development - Larson, Leila M.; Frongillo, Edward A.; Akter, Fahmida; Wooten, Shelbie; Brander, Rebecca L.; Ruel, Marie T.; Leroy, Jef L. (Elsevier, 2025)
Growth monitoring and promotion (GMP) visits provide a frequent contact point with caregivers which can be an opportunity for the promotion of early child development (ECD). Using a combination of quantitative analyses of longitudinal and cross-sectional data and a review of the literature, we investigated whether the GMP platform could improve ECD by identifying children at risk of poor development and delivering responsive parenting education to caregivers of young children. Cross-sectional and lagged regression analyses and area under the receiver operating characteristic curves (AUCs) indicated that growth indices were not accurate predictors of concurrent and later child development. Rather, validated tools, such as the Ages and Stages Questionnaire or the Survey of Well-being of Young Children, could be utilized during GMP visits to screen individual children for suboptimal development. Through a review of published literature on ECD interventions, we identified 10 light-touch ECD interventions which could feasibly be implemented during GMP visits, but only half have been evaluated for their effectiveness. Our findings demonstrate that, while growth indices cannot accurately identify children at risk of suboptimal development, the GMP platform could offer an opportunity to screen children for suboptimal development and to deliver ECD interventions. Further evidence on the implementation and effectiveness of light-touch parenting programs, however, is required.